Profile of Pregnant Women with Gestational Diabetes Mellitus at Increased Risk for Large for Gestational Age Newborns - Tavares, Maria da Glória Rodrigues; Lopes, Érika Sales; Barros, Rosy Anne de Jesus Pereira Araújo; Azulay, Rossana Santiago de Sousa; Faria, Manuel dos Santos (Revista Brasileira de Ginecologia e Obstetrícia / RBGO Gynecology and Obstetrics, 2019)
Objective Gestational diabetes mellitus (GDM) is associated with a higher risk of perinatal morbidity and mortality, and its main complication is the occurrence of large for gestational age (LGA) newborns. The present study aims to characterize pregnant women with GDM and to identify factors associated with the occurrence of LGA newborns in this population.Methods A cross-sectional study was performed based on medical records of women whose prenatal care and delivery were performed at the Maternal and Child Unit of the Hospital Universitário of the Universidade Federal do Maranhão, state of Maranhão, Brazil. A total of 116 pregnant women diagnosed with GDM were included according to the criteria of the International Association of Diabetes and Pregnancy Study Groups (IADPSG).Results The variables associated with LGA newborns after multivariate analysis were: obesity prior to pregnancy (OR = 11.6; 95% CI: 1.40–95.9), previous macrosomia (OR = 34.7; 95% CI: 4.08–295.3), high blood glucose levels in the 3rd trimester (OR = 2,67; 95% CI: 1.01–7.12) and combined change in the oral glucose tolerance test (OGTT) (fasting + postdextrose) (OR = 3.53; 95% CI: 1.25–14.2) = 1.17–10.6). Otherwise, insufficient weight gain during pregnancy reduced the risk for LGA newborns (OR = 0.04; 95% CI: 0.01–0.32).Conclusion Obesity prior to pregnancy, previous macrosomia, high blood glucose levels in the 3rd trimester, and combined change in the OGTT were independent predictive factors for LGA newborns in pregnant women with GDM.
Keywords: gestational diabetes mellitus; oral glucose tolerance test; large for gestational age